'It is so bad to be Estonian:' parody music videos and remediated sites of national cultural memory on Estonian public broadcasting. Issue 2 (3rd April 2023) - Roos, Liina-Ly
ABSTRACT: This article examines two Estonian parody music videos that were broadcast in an annual sketch program Tujurikkuja (Mood Spoiler) on Estonian Public Broadcasting. The videos target narratives of exceptionalism and racism in contemporary Estonia. I discuss the role that public broadcasting has in the formation of national cultural memory and argue that the mode of parody music videos has a complex potential to make visible the multi-imaged and multi-voiced discourses present in otherwise homogenous remediations of national cultural memory. Furthermore, the parody, satire, and carnival of the videos is extended as they are made available on YouTube.